DEVELOPMENT OF AN EDUCATIONAL TESTING WEB APPLICATION FOR AN EDUCATIONAL INSTITUTION - VOYTSIKHOVSKA , Lena; DZYUBA, Viktoria (Cherkasy University Bulletin: Applied Mathematics. Informatics, 2024)
Introduction. The fast pace of modern life is forcing us to adjust our plans and daily routines, compelling us to temporarily or permanently relocate, spend several hours in shelters, set priorities wisely, and conserve electricity. The whole world, including Ukraine, is currently undergoing a phase of digitalization so that anyone can handle basic tasks without leaving home. This includes shopping, filing paperwork, scheduling appointments with specialists, and similar activities. In this way, to some extent, we can ensure a successful balance between safety and comfort in people’s lives. Education is also undergoing digitalization, because in the midst of such chaos, we must continue to learn and grow, regardless of location or the circumstances around us. To do this, everything we need must be in one place. Of course, technology cannot replace a teacher at this point, but supplementary materials, homework assignments, and grades–all hosted on a single website accessible to parents, students, and teachers–will simplify life and add flexibility to the educational process. This approach will save time and resources and be freely available to any educational institution or organization. Purpose of this article is to develop an informational and testing web application for an educational institution, equipped with basic and essential functionality, which can be further improved based on user feedback, professional development, and team expansion. Results. The article examines the development of a modern web-based educational platform designed to support interaction between students, teachers, and school administrators. It describes the main stages of system development, including the analysis of existing educational platforms, identification of their advantages and limitations, and formulation of requirements for a unified and scalable learning management system. The proposed system integrates core educational processes into a single platform, enabling users to manage schools, classes, subjects, assignments, tests, and communication within one ecosystem. The main features of the system include user registration and authentication, role-based access control (student, teacher, administrator), creation and management of classes, assignment distribution, test creation and evaluation, file sharing, and interaction through posts and notifications. The system also supports invitation mechanisms via email and ensures secure access through tokenbased authentication. Special attention is given to the architecture and implementation of the system, which is based on modern technologies such as PostgreSQL, Prisma ORM, Node.js, TypeScript, NestJS, React, Redux, Vite, and Material UI. These technologies provide high performance, modularity, and scalability of the system. The system also integrates additional services such as MinIO for file storage, Docker for containerization, and MailHog for testing email functionality. The client-side and serverside applications are designed as a unified full-stack solution ensuring consistent user experience across different devices. The testing results confirm the correct operation of all system modules, including authentication, role management, data processing, file handling, and communication features. The developed platform is fully functional and suitable for practical use in educational institutions. Conclusion. The article presents a study on the design and implementation of a unified educational management system for schools. The development of such a system addresses the fragmentation of existing educational tools and improves the efficiency of communication and data management within educational institutions. The proposed solution demonstrates the effectiveness of integrating various educational processes into a single digital platform, allowing users to manage academic activities in a structured and convenient way. This approach significantly simplifies interaction between students, teachers, and administrators while improving transparency and organization of learning processes. The main outcomes of the work include:  analysis of existing educational platforms and identification of their limitations;  formulation of functional requirements for a unified system;  design and implementation of a full-stack web application using modern technologies;  integration of authentication, role management, and educational workflows;  testing and validation of system functionality and usability. The results of the study confirm that the developed system improves the efficiency of educational process management and can be further extended with additional features such as analytics, mobile applications, and external integrations in the future.